1999
DOI: 10.1016/s0954-6111(99)90156-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the expression of lymphocyte activation markers in blood, bronchial biopsies and bronchoalveolar lavage: evidence for an enrichment of activated T lymphocytes in the bronchoalveolar space

Abstract: In this study healthy never-smoking subjects (n = 18) were recruited from a population study. Bronchoalveolar lavage (BAL), blood lymphocytes and bronchial biopsies, analysed both in the epithelium and lamina propria, were stained for T and B lymphocytes, natural killer (NK) cells and different subpopulations of T lymphocytes. In BAL, significantly higher proportions of T lymphocytes (CD3), T lymphocyte activation markers; HLA-DR, CD26+, CD49a+, CD54+ and CD69+, helper T (CD3+4+) and memory helper T lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Secondly, no significant differences were found between groups in any of the different markers studied in peripheral blood, whereas marked compartmentalisation was observed when blood and BALF samples were compared (tables 3 and 4). These observations agree with previous studies [29][30][31] and suggest that differences observed in BALF (previously discussed) are due to specific recruitment and/or local activation in the lungs.…”
Section: Cd25 Treg Cells In Copd B Barceló Et Alsupporting
confidence: 93%
“…Secondly, no significant differences were found between groups in any of the different markers studied in peripheral blood, whereas marked compartmentalisation was observed when blood and BALF samples were compared (tables 3 and 4). These observations agree with previous studies [29][30][31] and suggest that differences observed in BALF (previously discussed) are due to specific recruitment and/or local activation in the lungs.…”
Section: Cd25 Treg Cells In Copd B Barceló Et Alsupporting
confidence: 93%
“…Normal BAL fluid is characterized by a proportion of lymphocytes of 5-15% (22), which includes activated (23,24) and granzyme B geneexpressing (14) lymphocytes. The presence of such activated alveolar lymphocytes in the normal setting could explain the presence of low levels of granzymes in some healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of other co-stimulatory molecules and their ligands have been identified in recent years [12]. EKBERG-JANSSON et al [12] reported a greater proportion of T-lymphocyte activation markers (human leukocyte antigen (HLA)-DR, CD26+, CD54+, CD69+) in bronchoalveolar lavage (BAL) fluid compared with blood in nonsmokers.…”
mentioning
confidence: 99%
“…A substantial number of other co-stimulatory molecules and their ligands have been identified in recent years [12]. EKBERG-JANSSON et al [12] reported a greater proportion of T-lymphocyte activation markers (human leukocyte antigen (HLA)-DR, CD26+, CD54+, CD69+) in bronchoalveolar lavage (BAL) fluid compared with blood in nonsmokers. Moreover, GLADER et al [7] showed a clear correlation between expression of the activation marker CD69 on CD4+ T-cells and lung function (forced expiratory volume in one second (FEV1)) in current smokers with and without COPD, indicating smoking-induced impairment of T-cell activation.…”
mentioning
confidence: 99%